(untitled) (Proceedings of International Educators Conference, 2023)
Many theories have been proposed to explain what a natural monopoly is in fact and what fields should be deemed as appropriate occasions to this consideration. Although the literature covers a wide variety of theories related to the scope of natural monopoly, this review will use several of them to examine the existence of natural monopoly in the electricity distribution industry thoroughly. This issue really needs a focused investigation, because there are sufficiently more debates and perspectives on this topic.